2020
DOI: 10.1111/febs.15451
|View full text |Cite
|
Sign up to set email alerts
|

Better to keep in touch: investigating inter‐organelle cross‐talk

Abstract: The strategic importance for cellular organelles of being in contact with each other, exchanging messenger molecules, is nowadays well established. Different inter‐organelle cross‐talk pathways finely regulate multiple physiological cellular mechanisms, and their dysregulation has been found to underlie different pathological conditions. In the last years, a great effort has been made to study such organelle interactions, to understand their functional roles within the cell and the molecules involved in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 132 publications
0
13
0
Order By: Relevance
“…Originally, subcellular organelles were considered as independent entities within a cell, however, recent discoveries have shown that there are dynamic interactions between organelles. Organelles are in close proximity, and they dynamically come in contact, with each other through membrane contact sites, which are enriched in signaling molecules and ion channels ( Rowland and Voeltz, 2012 ; Prinz, 2014 ; Phillips and Voeltz, 2016 ; Muallem et al, 2017 ; Cohen et al, 2018 ; Lee et al, 2020 ; Rossini et al, 2021 ) ( Figure 1 ). Membrane contact sites serve as “hotspots” for the transfer of signaling molecules and crosstalk between organelles, which are essential for cellular homeostasis.…”
Section: Ca 2+ Dyshomeostasis Mediates the Vicious...mentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, subcellular organelles were considered as independent entities within a cell, however, recent discoveries have shown that there are dynamic interactions between organelles. Organelles are in close proximity, and they dynamically come in contact, with each other through membrane contact sites, which are enriched in signaling molecules and ion channels ( Rowland and Voeltz, 2012 ; Prinz, 2014 ; Phillips and Voeltz, 2016 ; Muallem et al, 2017 ; Cohen et al, 2018 ; Lee et al, 2020 ; Rossini et al, 2021 ) ( Figure 1 ). Membrane contact sites serve as “hotspots” for the transfer of signaling molecules and crosstalk between organelles, which are essential for cellular homeostasis.…”
Section: Ca 2+ Dyshomeostasis Mediates the Vicious...mentioning
confidence: 99%
“…Dysfunction of lysosomes results in the accumulation of aberrant proteins, lipids, and damaged organelles, especially mitochondria, leading to increased formation of toxic protein aggregates and excessive generation of reactive oxygen species (ROS), which are also crucially associated with neurodegeneration and neuronal death ( Lin et al, 2019 ; Ray et al, 2021 ). Furthermore, recent studies have highlighted the essential role of the interactions between the ER, mitochondria, and lysosomes in the maintenance of normal cellular homeostasis ( Raffaello et al, 2016 ; Rossini et al, 2021 ). However, dysfunction of one organelle has been shown to cause failure of the other two organelles, suggesting a switch-like mechanism or molecule in the cells.…”
Section: Introductionmentioning
confidence: 99%
“…This poor resolution over Z -axis can be improved by total internal reflection fluorescence microscopy (TIRFM), which has a longitudinal resolution smaller than 200 nm [ 21 ]. TIRFM uses the total reflection of light at the interface between water and glass to produce an excitation light called evaporation wave to selectively illuminate the surface of the PM-related MCSs [ 121 , 122 ]. The effective penetration depth of the probe wave is maintained within 100 ∼ 200 nm, avoiding the visualization of fluorescent proteins or structures deep within the cells, thus improving the accuracy [ 123 ].…”
Section: Approaches To Visualize Mcss In Fixed Samples and Living Cellsmentioning
confidence: 99%
“…The ER makes extensive contacts with other organelles such as mitochondria, the Golgi apparatus, and endosomes. These contact sites play essential roles in protein homeostasis, lipid transfer, metabolite shuffling, ion exchange, and signal transduction (Rossini et al, 2021). In contrast to these "contact sites" at which the ER membranes are tethered to, but not fused with the membranes of other organelles, the ER is linked to the nucleus via direct fusion to the outer nuclear membrane (ONM) of the nuclear envelope (NE) (Friedman and Voeltz, 2011).…”
Section: Introductionmentioning
confidence: 99%